2019
DOI: 10.3390/app9061076
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Salt Ions before Spraying Improves Heat- and Cold-Induced Gel Properties of Soy Protein Isolate (SPI)

Abstract: Spray drying is used in the food industry to convert liquids into dry powders. The effect of the addition of salt ions before spray drying to improve the heat- and cold-induced gel properties of soy protein isolate (SPI) was investigated. Certain concentrations of Na+ (0.005–0.01 M), Mg2+ (0.005 M), and Ca2+ (0.005 M) significantly increased the hardness, springiness, cohesiveness, chewiness, gumminess, resilience, and water holding capacity of the heat- and cold-induced gels. This effect arises predominantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 49 publications
(60 reference statements)
1
16
0
1
Order By: Relevance
“…Salt remains an important taste enhancer. However, when in contact with proteins, it affects their functionalities [ 22 ]. Current nutritional trends aim at reducing salt content and especially sodium, leading to some product formulation challenges, not only for sausage-types of products but also for comminuted products and whole-cuts.…”
Section: Meat Analogue Products Formulationmentioning
confidence: 99%
“…Salt remains an important taste enhancer. However, when in contact with proteins, it affects their functionalities [ 22 ]. Current nutritional trends aim at reducing salt content and especially sodium, leading to some product formulation challenges, not only for sausage-types of products but also for comminuted products and whole-cuts.…”
Section: Meat Analogue Products Formulationmentioning
confidence: 99%
“…Among the most importante plant-based protein ingredients are the soy protein isolates, which present interesting nutritional value and important functional properties, as previously discussed (CHEN ET AL 2017;MALTAIS;MALTAIS;MOURE et al, 2006;NISHINARI et al, 2014;ZHENG et al, 2019;ZHAO et al, 2021). RIOUX; MCCLEMENTS, 2006;SCHMITT et al, 1998).…”
Section: Cold-set Gelation Methods: Properties Of Salt Induced Gelsmentioning
confidence: 95%
“…In fact, several other studies also cite the gelling capacity as a crucial functionality of the SPI but reinforce the poor stability of the protein gels formed may limit its application in certain types of food WU et al, 2018;XIAO et al, 2020;ZHAO et al, 2021;ZHENG et al, 2019). However, it has been demonstrated that functional characteristics of the protein gel can be improved by the incorporation of polysaccharides to the systems, evindencing the importance of the continuous development of studies that investigate the gelling capacity of commercial SPIs to expand their application (GOUZY et al, 2019;ZHOU et al, 2014).…”
Section:  Chapter 9: General Conclusionmentioning
confidence: 99%
“…The gelation ability of soy proteins is important for the textural properties of food systems. Soybean proteins can form heat-induced and cold-set gels (Zheng et al, 2019).…”
Section: Chaptermentioning
confidence: 99%
“…Calcium caseinate, which is treated with Ca(OH) 2 , allows the formation of a highly anisotropic structure (meat-like) in a shear cell device at 50°C. In contrast, sodium caseinate only forms an isotropic structure under similar processing conditions (Manski et al, 2007;Wang et al, 2019). This is indicative of the effect that the different hydroxides have on the properties of proteins.…”
Section: Introductionmentioning
confidence: 99%